Immuno-PET imaging of VEGFR-2 expression in prostate cancer with (89)Zr-labeled ramucirumab - Li, Miao (Am J Cancer Res, 2019)
The detection and monitoring of prostate cancer (PrCa) malignancies using most of the conventional strategies is challenging. As an over-expressed biomarker of PrCa, the vascular endothelial growth factor receptor 2 (VEGFR-2) can be delineated by non-invasive imaging to address such issue. Herein, we report the positron emission tomography (PET) of VEGFR-2 expression in a PrCa mice models by composing a novel tracer, [(89)Zr]zirconium-labeled clinical VEGFR-2 antibody (Ramucirumab), i.e. (89)Zr-Df-R. The VEGFR-2 expression levels among three different PrCa cell lines (PC-3, LNCAP and LAPC-4) were confirmed by flow cytometry. The immuno-PET imaging and bio-distribution (Bio-D) study were conducted in subcutaneous PrCa mice models via the (89)Zr-Df-R. The regions of interest (ROI) data showed that the uptake of (89)Zr-Df-R in the positive PC-3 (9.5±3 %ID/g) tumors are obviously higher than those ones in the negative LNCAP (6.0±1.7 %ID/g) or LAPC-4 (4.3±0.7 %ID/g) tumors at 120 hours post-injection, while the accumulation of (89)Zr-Df-R in PC-3 tumors (4.3±1.2 %ID/g)) could be significantly reduced by the blockade of unlabeled Ramucirumab. These quantitative data coincide with the Bio-D data and proves the specificity. Additionally, the immuno-fluorescent staining results confirmed the expression pattern of VEGFR-2 among various PrCa tumors. Finally, the flow cytometry of PC-3 tumor tissue further proved that the binding of (89)Zr-Df-R to VEGFR-2 primarily occurs on the PC-3 tumor cells. In summary, the description of the VEGFR-2 expression in PrCa by in-vivo PET with (89)Zr-Df-R is feasible and it may shed light on the early detection of foci and dynamic monitoring of anti-VEGFR-2 therapy in PrCa.